Clinical Validation of Reduced Alcohol Consumption After Treatment for Alcohol Dependence Using the World Health Organization Risk Drinking Levels. (26th December 2016) - Witkiewitz, Katie; Hallgren, Kevin A.; Kranzler, Henry R.; Mann, Karl F.; Hasin, Deborah S.; Falk, Daniel E.; Litten, Raye Z.; O'Malley, Stephanie S.; Anton, Raymond F.
Abstract : Background: Alcohol use disorder (AUD) is a highly prevalent public health problem associated with considerable individual and societal costs. Abstinence from alcohol is the most widely accepted target of treatment for AUD, but it severely limits treatment options and could deter individuals who prefer to reduce their drinking from seeking treatment. Clinical validation of reduced alcohol consumption as the primary outcome of alcohol clinical trials is critical for expanding treatment options. One potentially useful measure of alcohol treatment outcome is a reduction in the World Health Organization (WHO, International Guide for Monitoring Alcohol Consumption and Related Harm . Geneva, Switzerland, 2000) risk levels of alcohol use (very high risk, high risk, moderate risk, and low risk). For example, a 2‐shift reduction in WHO risk levels (e.g., high risk to low risk) has been used by the European Medicines Agency (2010, Guideline on the Development of Medicinal Products for the Treatment of Alcohol Dependence . UK) to evaluate nalmefene as a treatment for alcohol dependence (AD; Mann et al. 2013, Biol Psychiatry 73, 706–13). Methods: The current study was a secondary data analysis of the COMBINE study ( n  =   1, 383; Anton et al., 2006 ) to examine the association between reductions in WHO risk levels and reductions in alcohol‐related consequences and mental health symptoms during and following treatment in patients with AD. Results: Any reduction in WHO risk drinking level during treatment was associated with significantly fewer alcohol‐related consequences and improved mental health at the end of treatment and for up to 1 year posttreatment. A greater reduction in WHO risk drinking level predicted a greater reduction in consequences and greater improvements in mental health. Conclusions: Changes in WHO risk levels appear to be a valid end point for alcohol clinical trials. Based on the current findings, reductions in WHO risk drinking levels during treatment reflect meaningful reductions in alcohol‐related consequences and improved functioning. Abstract : As a chronic disorder, the optimal management of alcohol dependence should include reductions in alcohol consumption. The World Health Organization (WHO) risk levels provide targets for alcohol risk reduction that are strongly associated with meaningful reductions in alcohol‐related consequences. This figure shows the average Drinker Inventory of Consequences (DrInC) total scores by change in WHO risk level from baseline to end of treatment (left figure) and one year posttreatment (right figure).